Text Processing Application on Images using Modification of LSB and ROTI3 Methods - Suma, Muhammad Rizki; Sary, Yoshida (Hanif Journal of Information Systems, 2025)
This thesis is titled "Text Processing Application on Images Using Modified LSB and ROT13 Methods". This research aims to develop an application that can hide text messages within images using steganography techniques. The methods employed in this study are Least Significant Bit (LSB) for embedding messages into image pixels, and ROT13 for encrypting the message before embedding. By utilizing these two methods, it is expected that the hidden messages can be protected from unauthorized parties. The results of this research indicate that the developed application is capable of storing and retrieving messages effectively, while providing a higher level of security for the stored information. This research is expected to contribute to the fields of cryptography and steganography, and serve as a reference for future studies. The purpose and benefits of this research are to design and implement an application that is able to insert, encrypt, and extract text from digital images. Utilizing a combination of LSB (Least Significant Bit) and ROTI3 methods to improve efficiency and security in text processing on images.